Role of bladder washing cytology with fresh voided urine cytology in the diagnosis of urothelial malignancy (Journal of Fatima Jinnah Medical University, 2019)
Background: Bladder cancer is one the most common lesion treated by urologists. Since decades cystoscopy has been the gold standard for the diagnosis of primary and recurrent urothelial cancers. Exfoliative urinary cytology of fresh voided urine and bladder washings is usually performed to preceding or to complement cystoscopy. This study aims to determine the role of exfoliative cytology of fresh voided urine and bladder washings in the diagnosis of primary and recurrent urothelial malignancy and to compare the diagnostic efficacy (sensitivity, specificity) of bladder washings cytology with voided urine cytology in the diagnosis of urothelial carcinoma. Patients and methods: The study was performed in the department of Pathology, Allama Iqbal Medical College, Lahore in collaboration with the department of Urology, Jinnah Hospital, Lahore. Sixty patients of both genders above 45 years of age presenting with painless hematuria, imaging evidence of urinary bladder lesion or recurrent tumor were included. Fresh voided urine and bladder washings were obtained in all the cases and cytology was performed. Results: The sensitivity of voided urine cytology and was 94.7% and specificity 33.3% with positive predictive value of 96.4% and negative predictive value of 25%. The accuracy was calculated as 91.6%. The sensitivity, specificity, positive predictive value and negative predictive value for bladder washing cytology were 94.7%, 33.3%, 96.4% and 25% respectively. The accuracy for bladder washing cytology was the same as that of the fresh voided urine cytology (91.6%). Conclusion: Fresh voided urine cytology in patients with painless hematuria is a noninvasive, cost effective and readily available tests to detect the presence of any malignancy before further invasive work up. The fresh voided urine cytology and bladder washing cytology revealed same sensitivity, specificity and predictive values so noninvasive cytology of fresh voided urine may be recommended over bladder washing cytology which is an invasive procedure. urothelial tumor if superadded infection or any reactive atypia is present. It can be reported as suggestive or suspicious for low grade malignancy if the clinical history and radiologic investigations support a vesicle growth.
Keywords: Bladder washing; fresh voided urine; urothelial malignancy; cytology